Analysis of Gender Based Reading Interest Index for High School Students at West Sumbawa Regency in 2021 - Rizka Donny Agung Saputra; Enida Fatmalia (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The purpose of this study was to analyze the reading interest index, inhibiting factors and efforts to increase reading interest in high school students equivalent in West Sumbawa Regency. The research approach used exploratory descriptive and Field Research with survey methods. The population of this study consisted of 1,754 students spread over 21 schools, with the purposive sampling technique and the numbers were calculated using the Slovin formula, so the total sample was 325 students. The instruments used to collect research data were non-test instruments in the form of questionnaires, interviews and literature reviews. The research data were then analyzed by categorizing the reading interest index. The results showed that: 1) High school students equivalent in West Sumbawa district with Gender Women have a higher interest in reading than men, but the index of reading interest was still in the "moderate" category; 2) High school students and equivalent in Brang Rea, Jereweh and Sekongkang Sub-districts have the highest reading interest index than other sub-districts, but the reading index in the three sub-districts is in the “moderate” category; 3) The inhibiting factors for increasing students' reading interest are internal and external factors, namely internal factors including self-motivation and activity/busyness, while external factors are the environment, facilities and infrastructure, and lack of education; 4) The concrete efforts that have been made by the West Sumbawa Regency Government to increase interest in reading are the establishment of the "Pemasyarakatan Gemar Membaca bagi Siswa dan Masyarakat di Kabupaten Sumbawa Barat" several years ago but it has not been going well so it needs optimization so that the objectives of this program can be achieved.